Food waste to resource recovery: a way of green advocacy - Das A.; Verma M.; Mishra V. (My University, 2025)
Due to the massive growth in population and urbanization, there has been a huge increase in the volume of food waste globally. The Food and Agriculture Organization (FAO) has estimated that around one-third of all food produced each year is wasted. Food waste leads to the emission of greenhouse gas and depletion of the soil fertility. Nevertheless, it has immense potential for the recovery of high-value energy, fuel, and other resources. This review summarizes the latest advances in resource recovery from food waste by using technologies that include food waste–mediated microbial fuel cell (MFC) for bioenergy production. In addition to this, utilization of food waste for the production of bioplastic, biogas, bioethanol, and fertilizer has been also discussed in detail. Competitive benefits and accompanying difficulties of these technologies have also been highlighted. Furthermore, future approaches for more efficient use of food waste for the recovery of valuable resources have been also offered from an interdisciplinary perspective. © The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2023.